Are 80-Year-Old Swimmers Faster than 25-Year-Old Master Swimmers? (Baltic Journal of Sport and Health Sciences, 2018)
Competitive sport is one of the stimulants in making people practice exercise on the regular basis. Many of the handicap systems have been tried in different sports to match younger or older competitors to the young male adults, and it seems that the result indexing system according to age, which is in operation in track-and-field at the moment, is functional enough to help motivating veteran athletes to continue to participate in sports actively. The question raised by the authors of the present study was: “How can we create and implement coefficients and equations, which may be used to compare the results achieved by the master swimmers of different age groups?”. The aim of this study was to compile a point score system for the masters’ swimming results. Objectives: 1) to determine the changes in master swimmers’ (men and women) race times depending on age; 2) to calculate the coefficients for the conversion of the master swimmers’ (men and women) race time; 3) to offer the system of recalculation of converted master swimmers’ results in time into points, and to test the new ranking system in a Master swim meet. The data were taken from World Top-10 Masters Swimming Tabulation. Both male and female athletes were divided into 5-year age groups, starting from 25 years and going up to 94 years of age. We analysed the results (times) of the 1992—2005 year period in a cross-sectional study design. We calculated the differences in percentages of the averages of the results in different age group in comparison to the results achieved by the participants of the 25—29 year age group. Then we calculated the age coefficients, which could be used in indexing the competitive results, and finally we applied the International Swimming Federation (FINA) tables for point score to rank the master swimmers in actual competition. The research findings suggested that: 1. Among the women swimmers, a quicker deterioration of the results starts above the age of 75 years and older, and this decline is most obvious in breaststroke, butterfly, and individual medley, while it is less pronounced in long freestyle events. 2. For males, swimming performance also abruptly decreases after the age of 75 years. Differently from women, males degrade their freestyle sprinting abilities less than the results in long-distance freestyle swimming. The results in butterfly deteriorate the most in both genders, with the greatest decline seen again after the age of 75 years. 3. Here we have introduced a system for the recalculation of master swimmers’ results by using the age coefficients, with a subsequent conversion of the result into point score. The system can be successfully applied in determining the master swimmers’ rank among swimmers of different age groups.Keywords: results of master athletes, result indexing, swimming styles.